Height‐Integrated Ionospheric Conductances Parameterized By Interplanetary Magnetic Field and Substorm Phase. Issue 10 (7th October 2020) - Carter, J. A.; Milan, S. E.; Paxton, L. J.; Anderson, B. J.; Gjerloev, J.
Abstract: An understanding of ionospheric conductances is important for models of large‐scale dynamics in the Earth's magnetosphere. We parameterize height‐integrated Pedersen and Hall conductances in the ionosphere, derived from images of auroral emissions obtained by the Defense Meteorological Satellite Programme low‐altitude orbiting spacecraft, under different interplanetary and solar wind conditions. For the dayside, conductances are parameterized by interplanetary magnetic field clock angle and magnitude, and by season. These dayside conductances are compared to distributions of field‐aligned currents determined from measurements of the Active Magnetosphere and Planetary Electrodynamic Response Experiment. We use these currents to spatially determine a return flow region. We find that the return flow regions exhibit marginally larger conductances than those observed in the polar cap. Conductances in summer exceed those in winter for both the return flow and polar cap regions, on average by a factor of 1.2. On the nightside, we track changes in height‐integrated conductance across the Southern Hemisphere polar regions during an average substorm, following a substorm onset list derived from the SuperMAG database. Mean conductances peak approximately 0.75 hr after substorm onset, with maximum conductances seen in the 23 hr magnetic local time sector. Plain Language Summary: Low‐altitude spacecraft are able to build up images of aurora in the polar regions with low temporal resolution. Using a combination of these images taken in different wavebands, and after applying a model of atmospheric conditions, we can derive parameters such as ionospheric conductance, integrated along the line of sight from the spacecraft. Knowledge of conductances in the high‐latitude polar regions is important for our understanding of the large‐scale dynamics of the Earth's magnetosphere. We divide our results into two sections. The first section explores conductances in the dayside Northern Hemisphere under the effects of the incoming solar wind and interplanetary magnetic field. We compare these conductances to large‐scale patterns of ionospheric currents derived from a separate constellation of satellites. The currents can be used to define certain polar regions, and we compare conductances between these regions. The second section examines conductances under different phases of a substorm, when the magnetosphere is rearranged under the influence of particular driving conditions in the incoming solar wind. The behavior of the conductances is consistent with known patterns of substorm progression, and we show that peak conductances are seen half an hour after substorm onset. Key Points: The return flow region exhibits marginally larger conductances than those in the polar cap Peak conductances occur at 23 hr magnetic local time within 1 hr after substorm onset Conductances remain elevated at 02 hr magnetic local time for a prolonged period after substorm onset